Management protocols for status epilepticus in the pediatric emergency room: systematic review article - Cheuk C. Au; Ricardo G. Branco; Robert C. Tasker (Elsevier, 2017)
Objective: This systematic review of national or regional guidelines published in English aimed to better understand variance in pre-hospital and emergency department treatment of status epilepticus. Sources: Systematic search of national or regional guidelines (January 2000 to February 2017) contained within PubMed and Google Scholar databases, and article reference lists. The search keywords were status epilepticus, prolonged seizure, treatment, and guideline. Summary of findings: 356 articles were retrieved and 13 were selected according to the inclusion criteria. In all six pre-hospital guidelines, the preferred route of medication administration was to use alternatives to the intravenous route: all recommended buccal and intranasal midazolam; three also recommended intramuscular midazolam, and five recommended using rectal diazepam. All 11 emergency department guidelines described three phases in therapy. Intravenous medication, by phase, was indicated as such: initial phase - ten/11 guidelines recommended lorazepam, and eight/11 recommended diazepam; second phase - most (ten/11) guidelines recommended phenytoin, but other options were phenobarbital (nine/11), valproic acid (six/11), and either fosphenytoin or levetiracetam (each four/11); third phase - four/11 guidelines included the choice of repeating second phase therapy, whereas the other guidelines recommended using a variety of intravenous anesthetic agents (thiopental, midazolam, propofol, and pentobarbital). Conclusions: All of the guidelines share a similar framework for management of status epilepticus. The choice in route of administration and drug type varied across guidelines. Hence, the adoption of a particular guideline should take account of local practice options in health service delivery. Resumo: Objetivo: Esta análise sistemática de diretrizes nacionais ou regionais publicadas em inglês tem como objetivo entender melhor a diferença no tratamento do estado de mal epiléptico pré-hospitalar e no departamento de emergência. Fontes: Pesquisa sistemática de diretrizes nacionais ou regionais (janeiro de 2000 a fevereiro de 2017) contidas nas base de dados do Pubmed e do Google Acadêmico e listas de referência de artigos. As palavras-chave da busca foram estado de mal epiléptico, convulsão prolongada, tratamento e diretriz. Resumo do achados: 356 artigos foram identificados, e 13 foram selecionados de acordo com os critérios de inclusão. Em todas as seis diretrizes pré-hospitalares, o caminho preferencial de administração da medicação foi utilizar alternativas à via intravenosa: todas recomendaram midazolam bucal e intranasal; três também recomendaram midazolam intramuscular; e cinco recomendaram utilizar o diazepam via retal. Todas as 11 diretrizes de departamento de emergência descreveram três fases na terapia. No que diz respeito à medicação intravenosa, por fase, temos: fase inicial - 10/11 diretrizes recomendaram lorazepam e 8/11 recomendaram diazepam; segunda fase - a maioria (10/11) das diretrizes recomendou fenitoína, porém outras opções foram fenobarbital (9/11), ácido valpróico (6/11) e fosfenitoína ou levetiracetam (individualmente, 4/11); terceira fase - 4/11 diretrizes incluíram a opção de repetir a terapia da segunda fase, ao passo que as outras diretrizes recomendaram utilizar diversos agentes anestésicos intravenosos (tiopental, midazolam, propofol e pentobarbital). Conclusões: Todas as diretrizes compartilham uma estrutura semelhante para manejo do estado de mal epiléptico. A escolha da via de administração e do tipo de medicamento variou em todas as diretrizes. Assim, a adoção de uma diretriz específica deve levar em consideração as opções da prática local na prestação de serviços de saúde. Keywords: Status epilepticus, Seizure, Protocol, Guideline, Palavras-chave: Estado de mal epiléptico, Convulsão, Protocolo, Diretriz